Wound-healing activity of ethanolic and aqueous extracts of Ficus benghalensis - Vipin Kumar Garg; Sarvesh Kumar Paliwal (Wolters Kluwer Medknow Publications, 2011)
Wound healing is the process of repair that follows injury to the skin and other soft tissues. Following injury, an inflammatory response occurs and the cells below the dermis (the deepest skin layer) begin to increase collagen (connective tissue) production. Later, the epithelial tissue (the outer skin) is regenerated. There are three stages to the process of wound healing: inflammation, proliferation, and remodeling. Traditionally, Ficus benghalensis is used for wound healing. Since no detailed scientific data are available regarding the wound-healing activity of F. benghalensis, the present study was designed to explore the same. The wound-healing efficacy of ethanolic and aqueous extracts of F. benghalensis was evaluated in excision and incision wound models. The parameters studied include rate of wound contraction, period of complete epithelialization, and tensile strength of incision wound. Student's t test was used to analyze the results obtained from the present study and P<0.05 was considered significant. Both the ethanolic and aqueous extracts of F. benghalensis were found to possess significant wound-healing activity, which was evidenced by decrease in the period of epithelialization, increase in the rate of wound contraction and skin-breaking strength. The present study has demonstrated that the ethanolic and aqueous extracts of F. benghalensis have properties that render them capable of promoting accelerated wound-healing activity compared with placebo control.